(untitled) (Current Problems in Rail Vehicles, 2025)
The bogie type Y25 is one of the most commonly used bogies in freight wagons in Europe. Open Cylindrical Roller Bearings (CRB) NJ/NJP 130x240 are generally used. This conservative solution is known more than 100 years. This proven, but conservative solution requires regular overhauls and relubrication. To modernize this system, SKF has developed a CRU 130x240 enclosed roller unit that fully replaces NJ/NJP without the need for any modifications to the housing. The new solution brings a major advantage – an extended maintenance interval of up to 1.2 million kilometres or 12 years, whichever comes first. This bearing arrangement twice the maintenance interval compared to the current variant, which provides the end user with significant savings in maintenance costs.